Digital Business Transformation in Response to Global Business Dynamics at Mochi Mami MSMEs - Bunga Amirah; Kusmilawaty Kusmilawaty; Nur Ahmadi Bi Rahmani (Lembaga Riset Ilmiah, 2026)
Global economic uncertainty and raw material inflation challenge the sustainability of conventional culinary MSMEs. This study examines the digital business model transformation of Mochi Mami using the Business Model Canvas (BMC) framework and the Zero Marginal Cost Society paradigm. A qualitative case study approach was employed, with data collected through in-depth interviews with the business owner and 10 participants of the online recipe class, complemented by sales documentation and social media observations. The findings reveal a fundamental transformation from a product-based business to a knowledge-based business through digital recipe education. This strategy enabled the business to attract more than 6,000 participants within one year and expand its market to Malaysia, Vietnam, and the Philippines while significantly reducing dependence on fluctuating raw material costs. The transformation also strengthened business resilience by creating a scalable digital learning ecosystem with near-zero marginal costs. This study contributes to the literature by demonstrating how digital knowledge assets can serve as an alternative business model for culinary MSMEs to enhance sustainability and competitiveness. Practically, the findings provide a strategic reference for MSMEs seeking to improve resilience through digital business model innovation in the digital economy era.